Peran Kelompok Tani Dalam Meningkatkan Produktivitas Jagung di Desa Lembang Lohe, Kecamatan Tellulimpoe, Kabupaten Sinjai: The Role of Farmer Groups in Increasing Corn Productivity in Lembang Lohe Village, Tellulimpoe District, Sinjai Regency - Sofyan, Mardian; Megawati, Megawati; Nurdin, Fadilah (Jurnal Ilmiah Manajemen Agribisnis, 2025)
This study aims to analyze the role of farmer groups in increasing corn productivity in Lembang Lohe Village. Farmer groups function as learning classes, production units, and vehicles for cooperation. This research uses a quantitative descriptive approach with 80 respondents determined using the Slovin formula from a population of 695 farmers. Data were collected through observations, questionnaires, interviews, and documentation, and then analyzed using multiple linear regression. The results show that farmer groups significantly affect the increase in corn productivity. The coefficient of determination (Adjusted R²) is 0.595, indicating that farmer groups explain 59.5% of the variation in corn productivity, while 40.5% is influenced by other factors. Therefore, farmer groups play an important role in enhancing corn productivity in Lembang Lohe Village. Kata kunci :  kelompok tani, produktivitas jagung, kelas belajar, unit produksi, wahana kerja sama